Relationship between tests of physical qualities and physical match performance in elite Rugby League players - Gabbett, T. J.; Stein, J. G.; Kemp, J. G.; Lorenzen, C. (The Journal of Strength and Conditioning Research, 2013)
Previous investigators have reported significant relationships between tests of physical qualities and physical match performance in high-intensity, intermittent team sport (e.g., soccer) players. Although rugby league requires competitors to perform high-intensity running, unlike most other high-intensity intermittent team sports, the physical demands are significantly increased through the large amounts of tackling, wrestling, and grappling that players are required to perform during match play. This study investigated the relationship between tests of physical qualities and match performance in professional rugby league players and determined whether running capacities were associated with the collision and repeated high-intensity effort demands of match play. Thirty-eight elite rugby league players (mean ± SD, age, 23.1 ± 2.7 years) performed tests of repeated sprint ability (12 × 20-m sprints on a 20-second cycle), prolonged high-intensity intermittent running ability (8 × 12-second shuttle sprints on a 48-second cycle), and estimated maximal aerobic power (VO2max) (multistage fitness test). Global positioning system data were collected during 16 professional rugby league matches. Players with better, prolonged, high-intensity intermittent running ability covered greater total distance and greater distance in high-speed running during match play. However, inconsistent relationships were found between tests of running abilities and other match performance variables, with prolonged high-intensity running ability (negative), VO2max (positive), and repeated-sprint ability (no relationship) differentially associated with the total number of collisions and repeated high-intensity effort bouts performed in competition. These findings demonstrate the importance of prolonged high-intensity running ability to the match running performance of elite rugby league players but also highlight the need for game-specific conditioning to prepare players for the high-intensity collision and repeated-effort demands of the game.